The Analysis of Code-Switching and Code-Mixing in a Fanfiction Entitled “Crazy Rich Chenle” - Shareen Vanessa, Shareen; Mulyawan, I Wayan; Ni Ketut Alit Ida Setyaningsih, Ni Ketut (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021, 2021)
This article is entitled “The Analysis of code-switching and code-mixing in a fan-fiction entitled “Crazy Rich Chenle””. This study aims to analyze the types of code-switching, types of code-mixing as well as the reasons of code-switching and code-mixing. The data is taken from the fan-fiction entitled “Crazy Rich Chenle”, written by Hadids and uploaded on the online reading platform known as “wattpad”. The documentation method and note-taking technique being used to collect the data. The data were analyzed using descriptive qualitative methods. This study uses the theory of Hoffman (1991) about types of code-switching and the theory proposed by Musyken (2000) about types of code-mixing. The result of this study showed that there are three types of code-switching and three types of code-mixing found and used by the characters in the fan-fiction “Crazy Rich Chenle”. The characters in the fan-fiction “Crazy Rich Chenle” mostly used inter-sentential switching and insertion types of code-mixing